(untitled) (Bangladesh Journal of Medical Science, 2012)
Aim:To assesses the efficacy of a relatively new drug-Febuxostat in management of gout and its comparison with allopurinol. Method: A comparative study of both Allopurinol and Febuxostat was done on 100 patients of gout. Both were studied for efficacy. side effects and for gout flare up. Results: Primary efficacy end point (baseline values) - a serum urate concentration of less than 6.0mg per deciliter at the last three measurements was reached by 54 %( 27/50) of group A patients taking 80mgs of febuxostat and 25 %( 12/50) of group B patients taking allopurinol 300mgs per day (P<0.001) Secondary efficacy end point(follow up values)- At first visit( after 2 weeks of onset of study), the proportions of subjects with serum urate concentration of less than 6.0mg/dl was significantly higher in the group A receiving febuxostat than the group B receiving allopurinol(P<0.001)[Tableno-1]. Conclusion: Febuxostat, at a daily dose was more effective than allopurinol at the commonly used fixed daily dose of 300 mg in lowering serum urate. Results of side effects and gout flare up were similar in both groups. Key words: Allopurinol; febuxostat; uric acid; gout DOI: http://dx.doi.org/10.3329/bjms.v10i4.7522 BJMS 2011; 10 (4): 257-259